HYPOXIC-ISCHEMIC ENCEPHALOPATHY IN NEONATES BORN TO SEVERE BIRTH ASPHYXIA - A. A. Zarubin; N. I. Mikheeva; E. S. Filippov; T. A. Belogorova; A. S. Vanyarkina; A. A. Shishkin (Acta Biomedica Scientifica, 2017)
This article provides a literature review on the topic of hypoxic-ischemic encephalopathy (HIE). Hypoxic-ischemic brain damage of newborn belongs to one of the most important problems of anesthesiology and resuscitation of newborn babies. Despite progress, perinatal hypoxic-ischemic encephalopathy remains an important cause of child mortality and damage to the central nervous system resulting in a disability of children. HIE clinical signs are nonspecific, so the diagnosis is based on the combination of medical history, physical and neurological examination, laboratory data and neuroimaging techniques. Pathological stage runs when after undergoing asphyxia is the main purpose neuroprotective therapy. The first 6 hours of life of the child, born in asphyxia, is a therapeutic window for the stabilization of the vital functions of the body, during which therapeutic measures are most effective in reducing apoptosis of brain cells. The only method, relatively widely used and effective in infants with severe birth asphyxia, is controlled hypothermia. Published clinical studies show a statistically significant reduction in mortality and severe neuropsychiatric disability at 18 months of life in infants treated with hypothermia. The use of stem cells, the use of hypothermia in combination with xenon or erythropoietin improves neurological outcome: fewer deaths and serious damage to the nervous system. However, these techniques to date are in the experimental stage. Currently, the main task of neonatologists, anesthesiologists and intensive care specialists is not only saving newborn lives, but also creating conditions for proper growth and development of the child.